Well-being and Anticipation for Future Positive Events: Evidences from an fMRI Study - Luo, Yangmei; Chen, Xuhai; Qi, Senqing; You, Xuqun; Huang, Xiting (Frontiers in Psychology, 2018)
Anticipation for future confers great benefits to human well-being and mental health. However, previous work focus on how people’s well-being correlate with brain activities during perception of emotional stimuli, rather than anticipation for the future events. Here, the current study investigated how well-being relates to neural circuitry underlying the anticipating process of future desired events. Using event-related functional magnetic resonance imaging (fMRI), forty participants were scanned while they were performing an emotion anticipation task, in which they were instructed to anticipate the positive or neutral events. The results showed that bilateral medial prefrontal cortex (MPFC) were activated during anticipation for positive events relative to neutral events, and the enhanced brain activation in MPFC were associated with higher level of well-being. The findings suggest a neural mechanism by which the anticipation process to future desired events correlate to human well-being, which provide a future-oriented view on the sources of well-being.